Psychological determinants in biathlon performance: A U23 national team case study - Abrahamsen, F. E.; Kvam, A.; Sæther, S. A. (Sports, 2024)
Background: The present investigation examined what psychological factors athletes perceived to impact their competition performance and what training strategies and focus the athletes considered to be the most important.